2019
DOI: 10.1002/hyp.13448
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of surface run‐off in the hydrological model ParFlow by a scale‐consistent river parameterization

Abstract: We propose an improvement of the overland‐flow parameterization in a distributed hydrological model, which uses a constant horizontal grid resolution and employs the kinematic wave approximation for both hillslope and river channel flow. The standard parameterization lacks any channel flow characteristics for rivers, which results in reduced river flow velocities for streams narrower than the horizontal grid resolution. Moreover, the surface areas, through which these wider model rivers may exchange water with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Overall, the model generally does not produce sufficient base flow compared to the GRDC observations (Figure 3), which we mainly attribute to the still coarse grid resolution compared to actual river widths (Schalge et al, 2019). The model does, however, produce reasonable daily mean discharge compared to GRDC data for rivers with catchment areas covered by the storm's precipitation.…”
Section: River Dischargementioning
confidence: 85%
“…Overall, the model generally does not produce sufficient base flow compared to the GRDC observations (Figure 3), which we mainly attribute to the still coarse grid resolution compared to actual river widths (Schalge et al, 2019). The model does, however, produce reasonable daily mean discharge compared to GRDC data for rivers with catchment areas covered by the storm's precipitation.…”
Section: River Dischargementioning
confidence: 85%
“…Our current choice of Manning's coefficient in ParFlow (5.52 × 10 −4 h m −1/3 ) results in realistic average discharge throughout the year, albeit at too-low flow velocities. In order to compensate for this inconsistency, Manning's coefficient could be scaled such that the overland flow velocity in river cells equals the river flow velocity, as proposed by Schalge et al (2019), which improves the phasing between simulated and observed discharge and the discharge peak. Similarly, the hydraulic conductivity of the model's top layer for river cells could be scaled in order to reduce the loss of too much surface water to the subsurface caused by the too-wide river cells.…”
Section: Discussionmentioning
confidence: 99%
“…dkrz.de/WDCC/ui/cerasearch/q?query=neckar&page=0&rows=15 (last access: 11 April 2020). We use for this study available simulation results generated by the research unit FOR2131 (Schalge et al, 2016(Schalge et al, , 2018(Schalge et al, , 2019 over an area containing the Neckar catchment in southwestern Germany in its center (Fig. 1).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The platform, specially designed for high-performance computing environments (Gasper et al, 2014), has been extensively evaluated against observations (Sulis et al, 2015;Shrestha et al, 2018a) as well as similar regional terrestrial system models (Sulis et al, 2015). The effect of spatial resolution on simulated soil moisture and the resulting exchange fluxes between land and atmosphere has been studied with TerrSysMP by Shrestha et al (2014Shrestha et al ( , 2018b.…”
Section: Virtual Realitymentioning
confidence: 99%